Time intergration schemes for rate dependent elasto-plastic constitutive equations - Hulley, Derek (Department of Mechanical Engineering, 2016)
The purpose of this thesis is to set out the results of an investigation into the commonly used methods of performing material update calculations within the framework of the Finite Element Method, as well as an investigation into possible new methods of performing the material update procedures within the context of a rate dependent plastic material obeying the Von Mises yield condition. Material update procedures which have been used and analysed frequently are the Generalised Midpoint Algorithm, including the Midpoint Method, the Trapezoidal Rule and the Backward Euler Method with Radial Return. Each method displays its own advantages when applied to different input parameters (being material properties, initial stresses and strains, and increments in time and strain).